When does the carrying out of transactions for consideration give rise to an economic activity relevant for VAT purposes? An insight into the relationship between the notions of consideration and income according to the Court of Justice of the EU. (2nd January 2017) - Mantovani, Matteo
ABSTRACT: The difference between consideration and income is relevant for VAT purposes. A supply of goods or a provision of services is subject to VAT if it is carried out for consideration. An activity is economic when it is carried out for the purposes of obtaining income on a continuing basis. Supplying goods or services for consideration does not mean that such an activity is economic for VAT purposes and the person who carries it out is a taxable person. To this end, income has to be yielded from the activity. The Court of Justice of the European Union has recently addressed the issue of the difference between income and consideration in two similar cases. Starting from these cases, the article analyses the concepts of consideration, economic activity and taxable person, and their mutual relationships, with a view to explaining when carrying out transactions for consideration gives rise to an economic activity relevant for VAT purposes and, as a consequence, the person who runs the activity becomes a VAT taxable person.